Rusya’nın Eçmiyazin Katoğikosluğuna Nüfuzu ve İstanbul Ermeni Patrikhanesinin Tesiri - Kılıç, Davut (Atatürk Kültür Merkezi Başkanlığı, 2000)
[Abstract Not Available]
Penetration of the Russia to Eçmiyazin and the influence o f İstanbul and Armenian patriarch